GAMBARAN KEJADIAN NYERI PUNGGUNG PASCA sectio caesarea DENGAN TINDAKAN SPINAL ANASTESI - Abdul gani kurniawan; Amin Susanto; Arni Nur Rahmawati (Jurnal Cakrawala Ilmiah, 2023)
Sectio caesarea is a method of giving birth to a fetus by making an incision in the uterine wall through the front of the abdomen or vagina. mothers after sectio caesaria will experience low back pain due to spinal anesthesia procedures. To describe the incidence of back pain after sectio caesarea with spinal anesthesia at Sejiran Setason Hospital, West Bangka The method used in this study is a descriptive analytical. Through a survey using an observation sheet with a cross sectional approach. The population in this study were all patients who underwent sectio caesarea with spinal anesthesia at Sejiran Setason Hospital, West Bangka, with a total of 30 respondents The results of this study obtained an overview of the number of age characteristics of the respondents mostly in the 18-24 year age group reaching 50%. The description of the level of pain experienced by the respondents, most of the respondents felt the level of moderate pain reached (43.3%) the age group experiencing the incidence of pain was mostly in the 18-24 year age group with moderate pain reaching 23.3%.: It can be concluded that the respondent's age, back pain level, age group and number of births affect the incidence of back pain after cesarean section with spinal anesthesia